Potret Tradisi Ari Ana Mahun (Maulid Anak Kecil) Di Negeri Kilkoda Kecamatan Pulau Gorom - Ade Salma Renati Kasongat; Muhamad Yusuf; Zulihi Zulihi; Suparto Iribaram; Rahmalia Ayu Isnaini; Rachmad Surya Muhandy (Ri'ayah: Jurnal Sosial dan Keagamaan, 2026)
The purpose of this research is to comprehensively explain the form of implementation of the Ari Ana Mahun tradition in Kilkoda village, Gorom Island sub-district. The type of research conducted is by using qualitative methods, with data collection techniques using passive participatory observation, indept interviews and documentation. Data analysis techniques use a flow model that divides into three parts, namely: Data reduction, data display, and conclusion drawing/verification. Research results: The Ari Ana Mahun tradition of the Kilkoda community is a cultural heritage that combines religious, social and spiritual values in harmony. The whole series of activities reflects the relationship between humans, God, and the community, and becomes a means of preserving identity and social solidarity. Timing based on the Hijriyah calendar shows the role of religion as a source of social order. The value of mutual cooperation can be seen in the preparation of special foods, snacks and fruits that are full of symbolic and spiritual meanings as a medium of communication between the living and the dead. Pilgrimage activities, decorating containers, prayers, and tahlilan strengthen morality, collective sanctity, and social cohesion, while food distribution and planting raung symbolize alms, sincerity, and respect for ancestors as a form of communication of spiritual and social values of the Kilkoda community.This study examines the Ari Ana Mahun tradition through a social perspective in the formation of local Islamic identity within the Kilkoda community. The analysis of Ari Ana Mahun as a social and symbolic practice demonstrates how the tradition shapes identity, solidarity, and the construction of local Islam among the Kilkoda people. Furthermore, this research contributes to enriching the study of local Islam as a system of religious symbols that constructs the identity and social solidarity of the Kilkoda community.